Estrategias de marketing para lograr una ventaja competitiva en la empresa Corporación Integrar de Riobamba. - Zhagui Jiménez, Kevin Ismael (2023)
Nowadays, marketing strategies have evolved in such a way that staying in the traditional environment constitutes a limitation for the progress of organizations, which is why it is necessary to seek new marketing methods in a digital world, this premise gives rise to to the present investigation that is developed with the need to establish the degree of incidence of marketing strategies to achieve a competitive advantage in the company "Corporación Integrar" of Riobamba. The research method applied was hypothetical-deductive through mixed and descriptive research. Data collection was carried out by applying a 10-question survey to a population of 37 people, the information obtained was tabulated, generating tables and graphs. statistics that allowed reaching the results extracted from the source. The hypothesis raised in the investigation has been verified by means of the chi-square test, where the incidence of the dependent variable competitive advantages and the independent variable marketing strategies was verified. The company "Corporación Integrar" of the city of Riobamba, based on the results obtained, requires marketing strategies focused on the use of digital media, for this reason actions have been proposed aimed at the frequent use of internet channels that allow to enhance the image of the business, presenting relevant information that generates a competitive advantage with which current clients can be retained and attract the attention of new clients who are decisive entities for the achievement of business objectives and goals.